2020
DOI: 10.1108/sasbe-06-2020-0077
|View full text |Cite
|
Sign up to set email alerts
|

Toward digitalization in the construction industry with immersive and drones technologies: a critical literature review

Abstract: PurposeIn this study, a critical literature review was utilized in order to provide a clear review of the relevant existing studies. The literature was analyzed using the meta-synthesis technique to evaluate and integrate the findings in a single context.Design/methodology/approachDigital transformation in construction requires employing a wide range of various technologies. There is significant progress of research in adopting technologies such as unmanned aerial vehicles (UAVs), also known as drones, and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 98 publications
3
57
0
Order By: Relevance
“…Moreover, planning and observation of a construction task involve many miniature details where the approach of a worker becomes difficult, thus hindering the use of ImTs at that situation and place. However, in recent times, the integration of ImT's with technologies like drones has made access to remote locations at a site workable, and research in this direction will increase in the future [226].…”
Section: Research Domains Code Number Percentagementioning
confidence: 99%
“…Moreover, planning and observation of a construction task involve many miniature details where the approach of a worker becomes difficult, thus hindering the use of ImTs at that situation and place. However, in recent times, the integration of ImT's with technologies like drones has made access to remote locations at a site workable, and research in this direction will increase in the future [226].…”
Section: Research Domains Code Number Percentagementioning
confidence: 99%
“…To that end, a large portion of research has been conducted in the construction industry over the past twenty years on adopting these new and immersive technologies. As an example, Elghaish et al (2020) examined the digitization of the construction industry by implementing immersive technology and UAVs, with a focus on the potential implementation, either alone or in combination, of these technologies. It was demonstrated that this immersive technology could successfully be utilized for use in construction education, team collaboration, controlling project remotely, and examining end-users' requirements.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, detailed keywords referring to the technical aspects of urban planning were found as shown in the green cluster (Figure 3). Additionally, implementations were observed in several subcategories within urban planning such as Construction (Faris Elghaish, et al, 2020), Infrastructure (Greenwood, et al, 2019), Traffic (Barmpounakis, et al, 2016;Hubbard & Hubbard, 2020), and Agriculture (Tsouros, et al, 2019).…”
Section: Understanding Of Society 50mentioning
confidence: 99%